(untitled) (Journal of Geography and Environmental Management, 2018)
The article explored the development and territorial organization of kinds of modern agritourism in Northern Kazakhstan. Farmhouse stands out as one of the most promising types of tourism. Northern region is considered from the point of view of one of the basic national tourist product’s components. Are defined possibilities of optimal territorial organization of agritourism in Northern Kazakhstan on the basis of crop and livestock production, and designated conditions of the ensuring the efficient operation of local government in the field of agro-tourism development.